THE PHENOMENON OF MULTI-ETHNIC AND RELIGIOUS LIFE THE ACEH SINGKIL REGENCY - Rani Putri; Fajri M.Kasim; Mursyidin Mursyidin; Suadi Suadi; Abidin Nurdin (Malikussaleh Social and Political Reviews, 2022)
Aceh Singkil is one of the areas known as a multicultural area, consisting of various ethnicities, customs, languages, and religions. Such conditions are vulnerable to friction and threaten community harmony. Therefore, building awareness of tolerance is the best step to overcoming problems that can trigger conflict. This study will examine the meaning of tolerance in Aceh Singkil, using the theory of symbolic interactionism. The approach used in this study is a qualitative approach with a descriptive type, with primary and secondary data sources. The process of data retrieval is obtained through observation techniques, interviews, and documentation. The results showed that each group of people, namely the majority and minority, have an awareness of tolerance. The meaning of tolerance for the people of Aceh Singkil is: (1) appreciate and respect, (2) Communicate, (3) Be kind based on religious values, and (4) not annoying. Social activities related to religious values are not negotiable. on the contrary, activities outside religious values can be tolerated by the community.